Sustainable tourism in the valuable natural areas: strategies and implementation - Majdak, Piotr (Studia Ecologiae et Bioethicae, 2018)
The considerations presented in the article focus on issues related to the implementation of the assumptions of the concept of sustainable development in relation to valuable natural areas that perform tourist functions. The research interests focused on Finland and the United States of America. Due to the large diversity resulting from natural, geographical, spatial and organizational or political conditions - the presented catalog of practical solutions contains a comprehensive set of initiatives that implement in practice the assumptions of sustainable development. These include both activities resulting from the implementation of nationwide projects as well as initiatives implemented at the level of local associations. The presented solutions show that the assumptions of sustainable development are a source of valuable inspiration for practical activities, and the concept itself is not limited only to the discursive and theoretical aspects.